PRACTICE AND FORMATION MODELS OF PROFESSIONAL ORIENTATION OF SCHOOLCHILDREN (Journal of Economic Research & Business Administration, 2019)
The lack of demand on fresh graduates on the labor market and inability to interact under conditions of market relations is one of the acute problems among young generation. Life requires the ability to choose the sphere of his professional and labor activity, focusing on the needs of society and taking into account the prospects of material well-being as well as individual and personal development, i.e. ability of professional self-determination. However, the education system is not ready to provide effective assistance to high school students in choosing a profession, since the content of professional self-determination as the goal of education has not been clarified from the perspective of governmental program, there is no scientific and pedagogical foundations, professional self-determination have not been developed in terms of updating the national school.Most of the problems of professional self-determination are investigated mainly within the framework of vocational guidance, which is often regarded as an object, rather than a means of scientific management. The main goal of the article is to cope with the use of a generalized model of choosing a profession without taking into account the individual characteristics of a high school student, the lack of a differentiated approach to students with different levels of readiness for professional self-determination, as well as informational supply in the world of professions.These circumstances make it necessary to develop a dynamic model for the development of professional self-determination for senior schoolchildren.During the research it was found that up-to-date graduates need to “to try on”, that is, it is important to make them familiarize with profession’s ‘demo-version’ before making a final decision. This allows us to offer more active project activities for high school students, as well as considering the possibility of short-term internships or entity visits for graduates.